Implementation Model Learning Cooperative Type CIRC (Cooperative Integrated Reading And Composition) Accompanied Biology Comics Media To Improve Students' Learning Interest In Lesson Biology On Student Class VII-A - Fitria Lestari; Nopriyeni Nopriyeni; Mihir Ranjan Nayak; Andre Skana Purba; Meida Esterlina Marpaung (PT. TAROMBO RESEARCH DEVELOPMENT pak, 2026)
The aim of this study is to increase students' interest in learning biology lessons in class VII A of SMP Negeri 14 Surakarta through the application of model learning cooperative CIRC type accompanied by comic media biology on Environmental Pollution material. This research is a classroom action research which ongoing in 3 cycles. Each cycle consists of The four basic stages are planning, action, observation, and reflection. Research data collection used questionnaires, observation sheets, and interviews. Data validity was measured using triangulation techniques, namely method triangulation. Data analysis used descriptive analysis techniques. The results of this study show that in cycle I based on The observation sheet shows that the average percentage of students' learning interest in the class was 57.53%, 65.12% in cycle II (an increase of 7.59%), and 83.28% in cycle III (increase 18.16%). Temporary based on questionnaire, average The percentage of students' learning interest in cycle I was 71.04%, 71.77% in cycle II (an increase of 0.73%), and 73.66% in cycle III (an increase of 1.89%). The results of student interviews showed that students were happier and found it easier to in learning biology lessons. Students are also interested in learning, students also feel that learning during the action is an interesting activity. The conclusion of this study is that the application of the CIRC learning model accompanied by biology comic media on the material of Environmental Pollution can increase students' interest in learning in class VII A students of SMP Negeri 14 Surakarta